Lipid Metabolic Disturbances after Severe Mechanical Injury - V. V. Moroz; L. V. Molchanova; M. Yu. Muravyeva; Yu. V. Marchenkov; V. I. Reshetnyak (Общая реаниматология, 2006)
The purpose of the present investigation was to study the levels of triglycerides, cholesterol metabolism, a number of biochemical plasma parameters, and the elastic properties of the arterial wall in the late period in victims with severe mechanical injury (SMI) and impaired hemodynamics.Material and methods. The investigation included 13 persons who had experienced SMI and blood loss with impaired hemodynamics. This involved three stages: 1) at the end of the first day; 2) on days 15—30 following injury; 3) 1—5 years after SMI. The concentrations of triglycerides, total cholesterol, and high-density lipoprotein (HDL) cholesterol and the activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase were determined. Very low-density lipoprotein and low-density lipoprotein (LDL) cholesterols were calculated by the Friedwald formula. An oscillometric analyzer (APKO-8-RITs) was used to record central hemodynamic parameters and vascular elastic properties.Results. There was a decrease in cholesterol levels and an increase in AST and ALT activities at the end of the first day. The activity of alkaline phosphatase was in the normal range. There was a reduction in AST and ALT on days 15—30 after injury. Enhanced alkaline phosphatase activity was observed at the same time. There was a considerable decrease in HDL cholesterol with the normal level of LDL cholesterol. The level of total cholesterol was in the normal range. The activities of AST and ALT were in the normal range at Stage 3 following 1—5 years after injury. At the same time, the activity of alkaline phosphatase remained increased. The content of HDL cholesterol having antiatherogenic properties remained lower although this parameter tended to become normal: there was an average increase by 33.9%. There was a decrease in arterial wall compliance and an increase in the speed of pulse wave propagation in the group of the examinees.Conclusion. The change in biochemical parameters in victims in the late period after SMI suggests that there is a gradual tendency for the parameters of lipid metabolism to normalize. The results of a study of the elastic properties of the arterial wall are indicative of increased vascular rigidity in the victims in the late period after SMI along with hemodynamic disorders.